Comparison of cardiac amyloidosis and hypertrophic cardiomyopathy: retrospective analysis of cardiac and kidney lesion - E. V. Reznik; T. L. Nguyen; M. M. Kudryavtseva; G. N. Golukhov (Российский кардиологический журнал)
Cardiac amyloidosis performance is in many ways similar to hypertrophic cardiomyopathy (HCM), and therefore it is extremely difficult to distinguish these two diseases in practice. The present study was performed to identify features that aid in the differential diagnosis by analyzing clinical, electrocardiographic, echocardiographic and laboratory data in patients with systemic amyloidosis and HCM. In the study, 38 patients with cardiac amyloidosis and 80 patients with HCM were examined. It was found that symmetrical left ventricular (LV) wall thickening, granular and sparkling appearance of the myocardium and thickened heart valves were the best cardiac predictors, and age above 63 years, decreased glomerular filtration rate and proteinuria were the best non-cardiac predictors of cardiac amyloidosis, whereas low QRS voltage and pericardial effusion were of less clinical significance. Systolic anterior motion of the anterior mitral leaflet, asymmetric LV wall thickening, and electrocardiographic signs of LV hypertrophy were highly suggestive of HCM. Thus, standard noninvasive methods may be useful for identifying myocardial infiltrative processes and differentiating cardiac amyloidosis from HCM.